El método Viso-audio-gnósico-motor para el aprendizaje de la ortografía en estudiantes de la Unidad Educativa “Isabel de Godín", Riobamba, año lectivo 2022-2023 - Villa Paucar, Brayan Roberto (2023)
The research’s objective is to propose an activity guide with the application of the Visual-audio-gnostic-motor method for learning Spelling for students of the tenth year "G" of the "Isabel de Godín" Educational Unit. in the 2022-2023 school year. The research was carried out with a quantitative approach. The research design was non-experimental, with descriptive field research. The study population constituted the same sample as a finite number of 33 students. Data collection was carried out through the application of a questionnaire, through which it was possible to verify the shortcomings that the tenth-year "G" students present in terms of the application of spelling standards. Among the failures found in the students, it was possible to observe difficulties with the use of the letters S and C, differentiating the correct use of the letters B and V, and differentiating and correctly using homophonous words, among others. That is why, through this research, strategies are proposed that are based on the Gnostic–Motor method for learning Spelling for the students of the tenth year "G" of the Educational Unit "Isabel de Godín" in the 2022 – 2023 school year. It is concluded that the application of the Visual–Audio–Gnostic–Motor method allows the student to use all their senses to promote their knowledge since, in the classrooms, there are students who develop some insights. More than others, in this way, the method allows the student's visual, auditory, cognitive, and motor phases to work together to promote meaningful learning.